KONSEP KOMUNIKASI JURGEN HABERMAS DALAM IDE DEMOKRASI DELIBERATIF DAN TINDAKAN KOMUNIKATIF - Muhammad Ersyad Muttaqien (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
Jurgen Habermas is one of social science scholars in Frankfurt school. He has main focus to manifest deliberative democracy in which public participation is regarded as the rights of communication. Moreover, it is supposed to value justice, eleminate destructive domination, and manifest consencus. The research method employs descriptive analysis and It employs Habermas communication theory consisted of 1) basic communication, 2) political communication, 3) press system, and 4) communication competence. The result shows that the theory holds the principal of human rights, the technique of discussion and the implementation of social network either cultural or structural. The conclusion of this research is Habermas avoids communication exploiting human and proposing a certain kind of communication. Therefore, those orientations produce equality, high value of human rights, and transformative communication.